绩效评估在政府中的实践 = The practice of performance management in government - 耿 正 Geng, Zheng (2011)
绩效是管理的永恒主题。本文概述了绩效评估在地方政府中的构建和实践，在揭示传统绩效考核指标诸种弊端的基础上，剖析了基层政府绩效的内涵和影响其绩效指标体系的因素，分析了平衡记分卡在引入政府绩效评估体系中的局限性，提出将其与政府绩效预算有机结合，构建全面的基层政府绩效评估指标体系。这不仅对于深化政府绩效评估理论研究、拓展政府管理创新的视野，具有重大的理论价值，而且对于树立和落实科学发展观和正确政绩观、指导地方政府绩效评估实践、提升地方政府管理绩效、推进政府管理创新等等，均具有重要的实践意义。 The eternal theme of the performance of management. This article outlines the performance evaluation in local government construction and practice, reveal the shortcomings of traditional unite in performance index, based on the analysis of the basic meaning and impact of government performance indicator system, its performance factors, the introduction of the Balanced Scorecard Government Performance Evaluation System limitations proposed budget with the combination of government performance, build a comprehensive performance evaluation index system of grass-roots government. This is not only for deepening the theory of government performance measurement and expand the vision of government management innovation of great theoretical value, but also for establishing and implementing the scientific development concept and the correct view, guide local government performance assessment practices to enhance the performance of local governments to promote Government management innovation, etc., all have important practical significance.